The effect of realistic mathematics education on student's mathematical communication ability - Trisnawati, Trisnawati; Pratiwi, Rani; Waziana, Winia (Malikussaleh Journal of Mathematics Learning (MJML), 2018)
This study aims to obtain a description of the application of Realistic Mathematic Education (RME) that can improve students' mathematical communication ability. The type of research used is a classroom action research that refers to the design of Kemmis and Mc.Taggart research they are planning, action, observation, and reflection. The results showed that Implementation of mathematics learning with Realistic Mathematics Education (RME) approach that can improve mathematical communication ability is a mathematics learning that has been done in accordance with RME characteristics, That is: use of real context (teacher presents a contextual problem and ask the student to understand the given problem). use of mathematical models (the students modeling by using props to solve problem), use of student production and construction in learning (the teacher gives opportunity to all students to solve the problem, and invite students to deliver the answer), existence of interaction (interaction occurs between teacher and students, and between student one with another), and the existence of integration (combines one unit of mathematics with other units also have integrated with other scientific fields).